A web-based tool for the development of Intensity Duration Frequency curves under changing climate. (July 2016) - Simonovic, Slobodan P.; Schardong, Andre; Sandink, Dan; Srivastav, Roshan
Abstract: Intensity Duration Frequency (IDF) curves are among the most common tools used in water resources management. They are derived from historical rainfall records under the assumption of stationarity. Change of climatic conditions makes the use of historical data for development of IDFs for the future unjustifiable. The IDF_CC, a web based tool, is designed, developed and implemented to allow local water professionals to quickly develop estimates related to the impact of climate change on IDF curves for almost any local rain monitoring station in Canada. The primary objective of the presented work was to standardize the IDF update process and make the results of current research on climate change impacts on IDF curves accessible to everyone. The tool is developed in the form of a decision support system (DSS) and represents an important step in increasing the capacity of Canadian water professionals to respond to the impacts of climate change. Highlights: Climate change impact on IDF curves investigated. Standardized IDF update process. Two theoretical contributions incorporated: downscaling method and skill score computation method. Web based tool developed and implemented for updating IDF curves under climate change.